The Responses of The Islamic Higher Education Students Against The Interpretation of The Quran’s Violent Verses and Hadith in Riau - Zarkasih; Permana, Niki Dian; Nawi, Aliff; Vebrianto, Rian; Thahir, Musa (Universitas Islam Negeri Madura, 2021)
The understanding of spiritual doctrine becomes the reason, and it causes an escalation in violence in the name of religion. Misinterpreting the Qur'an verses causes the doer to legalize the violence they do. This article presents the responses of Islamic higher education students in Riau Province and Riau Islands about the interpretation of violent verses in the Qur’an and Hadith. The sample consisted of 251 students from UIN Sultan Syarif Kasim in Riau, STAIN Bengkalis, and STAIN Abdurrahman Saleh in Riau Islands using a random sampling technique. Using descriptive analysis, the students’ responses against the interpretation of violent verses were categorized as fairly positive at 61%. It indicates that 39% of the students had a negative response. Hence, this study recommends the importance of efforts to “neutralize” the students’ understanding of the three Islamic higher education in Riau to prevent their tendency to have harsh or even radical understanding and responses.